Analysis of Fish Stress Levels Based on Different Topographic Characteristics in Magelang Regency, Central Java - Waluyo, Waluyo; Hidayati, Sri; Armando, Eric (Fakultas Perikanan dan Ilmu Kelautan Universitas 17 Agustus 1945 Cirebon, 2025)
Environmental stressors are external factors that can negatively impact aquatic life, especially fish, as they are considered the main indicators of ecosystem health due to their sensitivity to environmental changes. The purpose of this study was to determine the level of stress in fish (especially catfish and tilapia) based on the blood glucose concentration of fish cultivated in Magelang Regency, Central Java. The data analysis used was spatial analysis to describe the spatial conditions of topographic parameters, air temperature, pond water temperature, and blood glucose concentration of fish (tilapia and catfish). Crosscorrelation multiple variable analysis was used to determine the correlation coefficient value between each parameter. The Crosscorrelation Multiple Variable Analysis method with the Pearson Product-Moment Correlation model. The results of the analysis of blood glucose concentration of catfish were 59.59 mg/dL and tilapia 87.80 mg/dL, so in general it can be concluded that the influence or correlation between water parameters on the level of stress of fish in the Magelang Regency area is tiny, which indicates that the condition of catfish and tilapia is not experiencing stress, where the average blood glucose is still at a normal level. The correlation coefficient value between water temperature and blood glucose of tilapia is -0.06, and that of catfish is -0.41, which means that the relationship between pond water temperature and stress levels of tilapia and catfish is fragile.